Francophonie and literature: Aimé Césaire and his literary trajectory - Méndez Vega, Mauricio (2023)
This article begins with a general introduction on the Martinican writer Aimé Césaire. It briefly mentions the research project: “Main writers of the Francophonie and their literary trajectory during the second part of the 20th century and the first half of 21st century” and succinctly explains the concept of Francophonie. This article is divided into six parts: the author, his literary production, awards and distinctions, geographical location and the historical context of Martinique, the Negritude movement and finally, the study and analysis of three poems of this great writer